The extraction of maxillary lateral incisors for the treatment of a Class II crowded malocclusion: a case report - Dave Heemanshu R.; Samrit Vilas D.; Kharbanda Om Prakash (Sciendo, 2015)
The extraction of an upper lateral incisor for orthodontic purposes is rare and must be adequately justified.